VARIASI KOSAKATA POLITIK DALAM PEMILU INDONESIA 2024 SEBAGAI BENTUK KREATIVITAS BERBAHASA - Hanifah, Riska Lulu; Kusumaningsih, Dewi; Sukarno, NFN (Widyaparwa, 2024)
The use of political vocabulary in the 2024 Indonesian election is starting to vary. Political vocabulary variations are found in public politics. Many do not realize that political vocabulary includes linguistic creativity. This study describes the sociolinguistic factors that affect language creativity in creating phonological, morphological, and semantic creativity. The method used is qualitative descriptive, with mass media data sources such as television, as well as social media such as Instagram and Twitter that discuss the creativity of political vocabulary in the 2024 Indonesian elections. Data collection techniques include listening, reading, and taking notes for mass media, as well as reading and taking notes for social media. Data analysis uses the Miles and Huberman model, through data reduction, data presentation, and conclusion drawn. The results of the study explain the sociolinguistic factors that affect language creativity. Linguistic creativity through a linguistic approach that describes phonological creativity, including differences in writing and speech resulting in variations in political vocabulary. Morphologically, it involves political compounding, and cronyism. Meanwhile, semantically, it includes synesthesia, denotative meaning, connotative meaning, and the use of slang. The variation of political vocabulary is expected to contribute to the public understanding the use of vocabulary that appears in political contexts.Penggunaan kosakata politik dalam pemilu Indonesia 2024 mulai bervariasi. Variasi kosakata politik banyak ditemukan dalam politik publik. Banyak yang tidak menyadari bahwa kosakata politik termasuk kreativitas berbahasa. Penelitian ini menguraikan faktor-faktor sosiolinguistik yang memengaruhi kreativitas bahasa dalam menciptakan kreativitas fonologis, morfologis, dan semantis. Metode yang digunakan kualitatif deskriptif, dengan sumber data media massa, seperti televisi serta media sosial, seperti Instagram dan Twitter yang membahas kreativitas kosakata politik dalam pemilu Indonesia 2024. Teknik pengumpulan data meliputi simak, baca, dan catat untuk media massa, serta baca dan catat untuk media sosial. Analisis data menggunakan model Miles dan Huberman, melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menjelaskan faktor-faktor sosiolinguistik yang memengaruhi kreativitas berbahasa. Kreativitas berbahasa melalui pendekatan linguistik yang menguraikan kreativitas fonologis, mencakup perbedaan penulisan dan cara ucap menghasilkan variasi kosakata politik. Secara morfologis, melibatkan pemajemukan politik, dan pengakroniman. Sementara itu, secara semantis, meliputi sinestesia, makna denotatif, makna konotatif, dan penggunaan bahasa slang. Variasi kosakata politik diharapkan memberi kontribusi pada masyarakat dalam memahami penggunaan kosakata yang muncul dalam konteks politik.